2024
DOI: 10.1037/tra0001517
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility predicts chronic anxiety and depression during the first year of the COVID-19 pandemic—A longitudinal investigation of mental health trajectories.

Abstract: Objective: The COVID-19 pandemic is a significant stressor, potentially putting the well-being of the general population at risk. However, a significant proportion of the population exhibits resilience, raising questions regarding psychological constructs that could contribute to resilient coping. Studies indicate that flexibility, defined as the ability to adapt to changing contextual demands by employing various emotional, cognitive, and behavioral strategies, may significantly contribute to coping with long… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 69 publications
(98 reference statements)
0
4
0
Order By: Relevance
“…In contrast to consistent calls for more research into resilience mechanisms 6,9,14,77,78 , such research is still almost absent. Research into different aspects of flexibility 33,34,72 might be interpreted as such a higher-level individual resilience mechanism, while research into social and societal resilience mechanisms is missing in studies on individual responses to societal challenges.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to consistent calls for more research into resilience mechanisms 6,9,14,77,78 , such research is still almost absent. Research into different aspects of flexibility 33,34,72 might be interpreted as such a higher-level individual resilience mechanism, while research into social and societal resilience mechanisms is missing in studies on individual responses to societal challenges.…”
Section: Discussionmentioning
confidence: 99%
“…The Perceived Ability to Cope with Trauma (PACT) 43 is a 20-item questionnaire that measures the ability to cope and apply various regulatory strategies flexibly on a 7-point scale ranging from 1 (unable) to 7 (extremely able). The scale's internal consistency in the current study was α = 0.91.…”
Section: Methodsmentioning
confidence: 99%
“…Studies on first responders and the general population that examined regulatory flexibility have demonstrated a significant link between low levels of regulatory flexibility and elevated levels of depression 43 , 44 . Moreover, it was found that regulatory flexibility moderates the relationship between traumatic exposure and the tendency to develop PTSD symptoms among first responders.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that a combination of trauma focused coping and forward focused coping predicts optimal adjustment following traumatic events [37]. This has been demonstrated in acute traumatic events (such as after 9/11) [38], general trauma exposures [39] and also during COVID-19 [40]. On the other hand, there is evidence that in states of CTS, forward focused coping may be more predictive of a resilience to PTSD symptoms [18].…”
Section: Individual Copingmentioning
confidence: 99%